THE INFLUENCE OF OCEAN CURRENTS TOWARDS DISTRIBUTION OF TOTAL SUSPENDED SOLIDS VERTICALLY IN CILALANANG ESTUARY, DISTRICT INDRAMAYU - Gentur Handoyo; Petrus Subardjo; Agus Anugroho Dwi; Muhammad Sulaiman (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTCilalanangriver located in the village of EretanWetan, District Indramayu. There are Fishery Harbor Beach (PPP) and shipping activities in this region is quite high. Activities in the PPP could potentially lead to silting due to the material carried by the river flow. The purpose of this study to determine the concentration of total suspended sediment (TSS) and the influence of ocean currents on the TSS in Cilalanang Estuary, District Indramayu. The research is located at coordinates 1080 4’ 53.400” EL -1080 5’ 50.215” EL and 60 19’ 26.709” SL - 6019’ 26.720” SL. The method used in this research is quantitative method. Analysis of the TSS is done by making the TSS distribution maps using ArcGIS10.5 and modeling ocean currents using MIKE 21. The results showed that the concentration of TSS at low tide toward the high tide is worth between 286-888 mg / l whereas when the high tide towards low tide worth between 348-553 mg / l. Dominant ocean current direction at the time of low tide to the hightide leads to the southwest. This causes TSS concentration coming out of the mouth of the river converge toward the southwest near the shore. In conditions of high tide toward low tide the dominant current direction leads to the northeast. This led to the spread of TSS concentration coming out mouth of the river away from the shore. Key words: Cilalanang River, IndramayuDistrict,Ocean Currents, Ocean Tides, Total Suspended Solids